You are on page 1of 18

 

 

 

 

2 ρ ∂t 2

a 2

s

2 ρ

∂x

2

i

=

2 τ ij

∂x i ∂x j

ρ τ ij a s

∂ρ + ∂ρv i

∂t

∂x i

= 0

ρ v i th v

∂v i

ρ

∂t

+ ρv j

∂v

i

∂x

j

=

∂p

∂x i

∂τ ij

∂x j

=

∂x j

(ij + τ ij )

p τ ij δ

[τ ]

τ ij = µ

∂v

i

∂x

j

+ ∂v j

∂x

i +

2

3

µδ ij

∂v

k

∂x

k

µ

v p p p 0

∂v i

ρ

∂t

+ v i

∂ρ i

∂t

+ ρv j

∂v

i

∂x

j

+ v i

∂ρv j

∂x j

=

∂x j

((p p 0 )δ ij τ ij )

τ I

I

τ ij = ρv i v j + (p p 0 )δ ij τ ij

∂ρv i

∂t

=

I

∂τ

ij

∂x j

τ ij = (p p 0 )δ ij

u

∂ρv i

+ t (p p 0 ) = 0

∂t

 

p

=

p p 0

 

ρ

= ρ ρ 0

p

ρ = c 2

p 0 ρ 0 c

p p 0 c 2 ρ ∂/∂x i

∂t ∂x i

(ρv i ) +

2

∂x

2

i

(c 2 ρ ) = 0

2 ρ

∂t 2

2

∂x

2

i

(c 2 ρ ) =

1

2

2

c 2 ∂t 2

∂x

2

i

(c 2 ρ ) = 0

ρ = ρ ρ 0 = 0

L ij = τ ij τ

ij

I

0

L ij = ρv i v j + ((p p 0 ) c 2 (ρ ρ 0 ))δ ij τ ij

L ij

∂ρv i

∂t

+ ∂τ ij

∂x i

=

(τ ij τ

ij )

I

0

∂x i

∂ρv i

∂t

∂x i

+

(c 2 (ρ ρ 0 )) =

∂L ij

∂x i

ρv i

1

2

2

c 2 ∂t 2

∂x

2

i

(c 2 (ρ ρ 0 )) =

2 L ij

∂x i ∂x j

v i

ρv i v j

e ij

((p p 0 ) c 2 (ρ ρ 0 ))

L ij ρv i v j

ρ

p

L o Π = Γ

L o Do

L ≡ Dt

Dt

Do

=

∂t + U

Dt

Π 1 ln

p

 

κ

p 0

Do 2 Dt 2
Do 2
Dt
2

∂ c 2 ∂ ∂x i ∂x i + 2
c
2
∂x i
∂x i + 2
∂U ∂ ∂x i ∂x 1 c 2 ∂x ∂ i
∂U
∂x i ∂x 1
c 2 ∂x ∂ i

x 1

c 2 = κRT o

∂Q

∂t

+

∂E

∂x +

∂F

∂y

+

∂G

∂z

=

∂E υ

∂x

+ ∂F υ

∂y

+ ∂G υ

∂z

Q =

ρ

ρu

ρυ

ρω

ρE

E =

ρu

ρu 2 + p

ρuυ

ρuω

(ρE + p)u

F =

ρυ

ρυu

ρυ 2 +

p

ρυω

(ρE + p)υ

G =

ρω

ρωu

ρωυ

ρω 2 +

p

(ρE + p)ω

E υ =

0

τ xx

τ xy

τ xz

xx + υτ xy + ωτ xz q x

F =

0

τ yx

τ yy

τ yz

yx + υτ yy + ωτ yz q y

G =

0

τ zx

τ zy

τ zz

zx + υτ zy + ωτ zz q z

q x q y q z

p 2 = p 1 2γM

s

2

γ + 1

γ + 1

ρ 2 = ρ 1

(γ + 1)M

s

+ 2

2

2

(γ 1)M

s

u 2 = c s 2(M

s

2

1)

2

(γ + 1)M

s

c s ρ 1 p 1 a 0

ρ 2 p 2 u 2

M s = c s /a 0

x > a 0 t t = 0

ρ(x, 0) = f(x)

ρ (x, 0) = g(x)

∂t

f = ρ 1 g = 0

ρ(x, t) =

ρ 2 , a 0 t < x < c s t

ρ 1 , x > c t

s

ρ 2 = ρ 1 +

1

2γp 1 (M

s

γ + 1

2

1)

2a 0 p 1 (M

s

2

2

1)

2

4ρ 1 (M

s

1)

1

2

a 0 c 2

s

2

(γ 1)M

s

+ 2

2

(γ 1)M

s

2

+ 2 (γ 1)M

s